Granice teoretycznego nasycenia = The limits of theoretical saturation - Pasikowski, Sławomir (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article is devoted to the possibilities and the limitations created by theoretical saturation of categories in the process of qualitative research. The sample size is presented as a signal o the saturation and the issue connected with the credibility research verification. The results of the investigation have been presented in the scope of the theoretical saturation achievement. The conclusion is the methodological saturations has great advantages, but also entails some risk of lowering the quality of research results and their reliability.
Keywords: nasycenie teoretyczne; badania jakościowe